Magnolia zotictla (Magnolia sect. Macrophylla, Magnoliaceae): a new species from the southern Sierra Madre Oriental, México - Sánchez-González, Arturo; Gutiérrez-Lozano, Marisol; Yescas, Reyna Domínguez; Hernández-Álvarez, Adriana Gisela; Ortega-Peña, A. Salomé; Vázquez-García, J. Antonio (Phytotaxa, 2021)
A new species of Magnolia from the southern Sierra Madre Oriental, Mexico, is described and illustrated, providing information about its habitat distribution, ecology, biogeography and conservation status. After 12 fieldwork expeditions near the border of the states of Hidalgo and Puebla, we have developed morphological, ecological and biogeographic data to support recognition of populations from Acaxochitlán, Hidalgo and Pahuatlán, Puebla as a distinct species of Magnolia sect. Macrophylla. A key to species of this section and a distribution map for Mexican taxa are provided. The species was assessed as critically endangered (CR).